MENYOAL KEPASTIAN HAK ATAS TANAH MASYARAKAT MELAYU ASLI: KAWASAN PESISIR KEPULAUAN REMPANG, BATAM BERDASARKAN KONSEPSI HUKUM AGRARIA NASIONAL - Ridha Wahyuni; Taupiqqurrahman Taupiqqurrahman; Ulfia Hasanah (Universitas Suryakancana, 2023)
The absence of legal certainty regarding the status of control and ownership of land by the indigenous Malay Rempang community means this condition has the potential to cause land ownership conflicts between the indigenous Malay community and the local government. On the one hand, the government claims that all land in the Batam authority area is state land so that the state has the authority to use it based on Management Rights status, but on the other hand, the community insists that the land they have lived on is the land inherited from their ancestors. If we refer to the concept of land control by the state based on the UUPA then the state in this context is only the party given the authority to regulate and determine land ownership rights and ownership of land rights can only be given to the community, including the rights of indigenous people. Therefore, the native Malay Rempang people who have lived for a long time on their ancestral land must receive protection from the government. The formulation of the problem in this research is;